2007
DOI: 10.1186/1471-2199-8-82
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of the Entamoeba histolytica EhrabB gene promoter

Abstract: Background: The Entamoeba histolytica EhrabB gene encodes for a Rab GTPase involved in phagocytosis. It is located at a virulence locus where the Ehcp112 gene is in the complementary strand at 332 bp of EhrabB start codon, suggesting a finely regulated transcription of both genes. However, the transcription regulation in this parasite is poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Whereas we found the GAAC box and the alternative Inr element, we did not find the TATA box and Inr element sequence in most of the RING E3s. Absence of these elements has been shown for other Entamoeba genes and it is also known that AT rich sequences of six base pairs or more can substitute for TATA activity in association with other control elements (Gómez et al 1998;Purdy et al 1996;Romero-Díaz et al 2010). Other than these known motifs, a number of motifs were identified with significant e-values (Online Resource 13).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas we found the GAAC box and the alternative Inr element, we did not find the TATA box and Inr element sequence in most of the RING E3s. Absence of these elements has been shown for other Entamoeba genes and it is also known that AT rich sequences of six base pairs or more can substitute for TATA activity in association with other control elements (Gómez et al 1998;Purdy et al 1996;Romero-Díaz et al 2010). Other than these known motifs, a number of motifs were identified with significant e-values (Online Resource 13).…”
Section: Discussionmentioning
confidence: 99%
“…The EhrabB gene is located in the complementary chain of the DNA fragment containing the Ehcp112 and Ehadh genes (Juarez‐Hernandez et al, ; Rodriguez et al, ). Furthermore, their regulatory sequences overlap (Flores‐Soto, Azuara‐Liceaga, Lopez‐Camarillo, & Orozco, ; Romero‐Diaz et al, ). Organisation of EhrabB , Ehcp112 , and Ehadh genes in the genome could suggest that the roles of the encoding proteins may be somehow linked; however, the functional relationship of the three proteins is not well known.…”
Section: Introductionmentioning
confidence: 99%
“…This 33 bp DNA fragment contains the only inverse repeat (TTC) of HSE that was found in the 5′ non-coding region of EhMLBP in addition to the repeats of the sequence GAA thus making this region to contain a perfect triplicate of HSE. The presence of HSEs has been reported in the promoter region of proteins that are not HSPs, such as interleukin-6 (A.A. Parikh, 1988), p35 (Chang et al, 2006) and E. histolytica Rab GTPase (Romero-Diaz et al, 2007). The results of a recent analysis on the whole-genome sequence of Drosophila melanogaster showed that only 10% of the genes that contain HSE are indeed upregulated by HS (Gonsalves et al, 2011).…”
Section: Ehmlbp Expression Is Regulated By Hsmentioning
confidence: 99%